2005
DOI: 10.1029/2005jd006059
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of iron solubility from observations and a global aerosol model

Abstract: Mineral aerosol deposition is the dominant source of iron to the open ocean. Soil iron is typically insoluble and understanding the atmospheric processes that convert insoluble iron to the more soluble forms observed over the oceans is crucial. In this paper, we model several proposed processes for the conversion of Fe(III) to Fe(II), and compare with cruise observations. The comparisons show that the model results in similar averaged magnitudes of iron solubility as measured during 8 cruises in 2001–2003. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
5
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(165 citation statements)
references
References 72 publications
10
147
5
3
Order By: Relevance
“…On the other side, it was impossible to isolate the fraction of dissolved iron directly emitted with anthropogenic sources from the fraction of dust dissolved iron formed in acidic air masses rich in anthropogenic pollutants, so the correlation between iron solubility and other acid species was complicated, which may not be simply presented as a linear correlation [64]. Other factors may also affect the iron dissolution reactions: Luo et al (2005) [65] concluded that in-cloud processing was a dominant factor for iron dissolution. In-cloud photochemical processes reducing iron to a more soluble state (Fe(II)) have been the focus of several experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, it was impossible to isolate the fraction of dissolved iron directly emitted with anthropogenic sources from the fraction of dust dissolved iron formed in acidic air masses rich in anthropogenic pollutants, so the correlation between iron solubility and other acid species was complicated, which may not be simply presented as a linear correlation [64]. Other factors may also affect the iron dissolution reactions: Luo et al (2005) [65] concluded that in-cloud processing was a dominant factor for iron dissolution. In-cloud photochemical processes reducing iron to a more soluble state (Fe(II)) have been the focus of several experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors may also affect the iron dissolution reactions: Luo et al (2005) [65] concluded that in-cloud processing was a dominant factor for iron dissolution. In-cloud photochemical processes reducing iron to a more soluble state (Fe(II)) have been the focus of several experiments.…”
Section: Acid Processingmentioning
confidence: 99%
“…Yet, there is a necessity to understand modeling performance in direct comparison against observations, because large gaps in ironrelated observations could be at least partly compensated by information from model simulations. Several studies report on direct point-to-point model-observations comparisons (Luo et al, 2005(Luo et al, , 2008Hand et al, 2004;Mahowald et al, 2009). Based on several model studies used to extrapolate observation data, Mahowald et al (2009) concluded that annual averaged model iron surface concentrations and daily averaged observations differ by a factor of 50-1000 %.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The iron solubility in dust increases due to clouds, solar radiation and polluted air (Gao et al, 2003;Luo et al, 2005;Jickells and Spokes, 2001;Desboeufs et al, 2001;Hand et al, 2004), but it could also depend on the time that dust spends in the atmosphere (Zhuang et al, 1992;. The atmospheric chemical processing of iron occurs in clouds because they provide a relatively high acidic environment.…”
Section: Iron Solubility and Atmospheric Processingmentioning
confidence: 99%
See 1 more Smart Citation